China pro-growth monetary policy and its asymmetric transmission - Kaiji Chen; Patrick Higgins; Daniel F. Waggoner; Tao Zha (Federal Reserve Bank of Atlanta, 2016)
China monetary policy, as well as its transmission, is yet to be understood by researchers and policymakers. In the spirit of Taylor (1993, 2000), we develop a tractable framework that approximates practical monetary policy of China. The framework, grounded in relevant institutional elements, allows us to quantify the policy effects on output and prices. We find strong evidence that monetary policy is designed to support real GDP growth mandated by the central government while resisting inflation pressures and that contributions of monetary policy shocks to the GDP fluctuation are asymmetric across different states of the economy. These findings highlight the role of M2 growth as a primary instrument and the bank lending channel to investment as a key transmission mechanism for monetary policy. Our analysis sheds light on institutional constraints on a gradual transition from M2 growth to the nominal policy interest rate as a primary instrument for monetary policy.
Keywords: E5; E02; C3; C13; 330; monetary transmission; endogenous switching; central government; institutional rigidities; GDP growth target; lower growth bound; nonlinear VAR; systematic monetary policy; policy shocks; heavy industries; investment; bank loans; lending channel; Geldpolitik; Geldpolitisches Ziel; Wirtschaftswachstum; Inflationsbekämpfung; Geldpolitische Transmission; China